Analysis of Students Chemical Literacy Skills with Scientific Information: Case Study During Covid-19 - Melati*, Husna Amalya; Erlina, Erlina; Thongsan, Nuchsara Choksuansup (Jurnal Pendidikan Sains Indonesia, 2024)
Chemistry education students as a future chemistry teacher should have a good science literacy/chemical literacy in order to deliver chemistry knowledge to be applied in the future. Therefore, this study describes the chemical literacy skills of students of the Chemistry Education Study Program. The aim of this study is to investigate the chemical literacy levels related to chemistry concepts through a case study of global information during the covid-19 pandemic. A range of chemical literacy aspects is measured, which include nominal (recognizing chemistry concepts); functional (defining key concepts); conceptual (utilizing chemistry knowledge to describe daily phenomena); multi-dimensional literacy (utilizing chemistry knowledge to analyze information in a short article or other reading sources). The research method of this study is quantitative descriptive. Participants of the study were 112 students of the Chemistry Education Program who had already taken basic chemistry courses. The instrument used to obtain data on students chemical literacy levels was questionnaires using the Likert scales (three options) and open-ended questions. The findings show that the percentage of students nominal, functional, conceptual, and multi-dimensional literacy skills are 78.21, 60.54, 51.48, and 44.08% respectively. The findings indicated that students chemical literacy skills are in the average range and need to be improved